How does value relevance of accounting information react to financial crisis? - Eugenio, Karl Louis (Animo Repository, 2019)
The relevance of financial reports rests on the value relevance of accounting information. Since accounting information is value relevant only when used by investors to reflect stock valuations, it takes trust from the users of financial information over the financial statements. The heightened volatility of markets during periods of financial distress or crisis raises the imperative to determine the value of financial information during these periods. The great recession of 2008 also victimized East Asia, and firm strategies were influenced by resulting economic shocks. In this study, we aim to determine how value relevance of accounting information differ before, during, and after the 2008 global financial crisis. We employed panel data regression analysis to cover selected accounting information and market valuation data of publicly listed non-financial firms in Asia for the years 2000 to 2016. We find inconsistencies in relative value relevance of Asian firms throughout the period, that is, before, during, and after the crisis. We recommend for future research to widen the scope of our study to include countries outside Asia. © 2019 by De La Salle University.